Implementasi Aplikasi Monitoring Nilai dan Kegiatan Siswa Berbasis Android dengan Metode Prototype - Juniawan, Fransiskus Panca; Sylfania, Dwi Yuny; Rian Chrisna Putra, Rendy; Sulaiman, Rahmat (Jurnal Komtika (Komputasi dan Informatika), 2021)
The number of smartphone and internet users in Indonesia is currently very large. This is become the basis for the use and development of mobile-based applications for the advantage of education. However, not all High Schools in Indonesia have a mobile-based system. Another problem is that most of them still use conventional methods in implementing teaching and learning activities, and reporting learning outcomes to parents. This is also still the case at SMA Negeri 1 Pangkalanbaru, Bangka Tengah. This problem is what we want to raise and solve by developing applications that can solve these problems. The research was developed using the Prototype method which consists of stages of Data Collection, Rapid Planning, Prototype Design, and Prototype Testing. By using the UML tool, results are obtained in the form of parents who can monitor grades, school information, and school announcements. In addition, students can take attendance online, register for extracurricular activities, and view announcements. From the testing results it is known that the system performance is running well as it should.